Unsteady Computational Fluid Dynamics of the axial flow generated by the rotation of an arm in swimming - Samson, M.; Monnet, T.; Lacouture, P.; David, L. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
In swimming, it has been shown experimentally that the arm rotation induce significant axial flow along the arm toward the hand, which acts favorably on propulsion (Toussaint et al., 2002). The purpose of this paper is then to numerical study the role of the axial flow on the propulsion of the hand and the forearm from a simple rotational movement. This study is based on unsteady RANS methodology (Samson et al., 2017). A comparison was made between two simulations in translation and rotation conditions. Velocities and depths of the hand were chosen so as to approach the actual conditions of swimming: the hand velocity is equal to 2.5 m/s, and rotational velocity is equal to 5 rad/s. Pressure, force and the spatio-temporal evolution of the vortices were used to the analysis. The results of the velocity fields of the flow show the presence of the axial flow along the hand and forearm in rotational configuration, but not in translation. The dynamic pressure gradients between the dorsal side of the hand and the elbow are higher in the rotational configuration (close to 2500 Pa) than in translation (close to 0 Pa). The hydrodynamic forces applied to the hand are greater in rotation than in translation (43 N vs 37 N respectively). At the beginning of the movement, two vortices are present all along the suction surface of the forearm and hand (a leading edge vortex on the little finger side and a trailing edge vortex on the thumb side). Next, these structures detach and are shedded into the wake. In both configurations, due to an accumulation of vorticity, a complex entanglement of vortex structures appears on the dorsal side of the hand. In the rotating configuration, there is more vortices on the dorsal side of the hand relative to the translation configuration. This can be explained by both the effect of the axial flow which translates the vorticity towards the fingertip, and at the same time the effect of the tip vortex at the fingertip which prevents the release of this vorticity (Von Ellenrieder et al., 2003).